Microvascular decompression: a surgical option for refractory hypertension of neurogenic etiology. (May 2013) - Barley, Jessica; Ellis, Charles
Essential or unexplained hypertension exists in a significant segment of the US population. Among those with essential or unexplained hypertension is a subset of patients who are diagnosed with 'refractory hypertension' (RHTN) or uncontrolled hypertension despite sustained therapy with at least three antihypertensive agents. Neurogenic etiologies are prevalent among patients with RHTN, with a notable proportion requiring surgical intervention to normalize their blood pressure. Microvascular decompression (MVD) has emerged as a surgical intervention that may be efficacious for the treatment of RHTN. A review of studies reporting outcomes associated with MVD as a treatment approach for refractory hypertension of neurogenic causes (RHTN-N) suggests that blood pressure can be normalized after MVD in some patients with RHTN-N. Consequently, additional studies are needed to offer additional evidence to support MVD as an effective surgical intervention for difficult-to-treat patients with RHTN-N.